The Heterogeneity of the Intra-European Trade Network Since the Adoption of the Euro - Maveyraud , Samuel; Rondeau , Fabien (Studia Oeconomica Posnaniensia, 2026)
This paper investigates whether the extensive margin of intra-European trade can be considered as homogeneous (CEPII-BACI (1997-2013)). The following lessons can be drawn: the weighted network is heterogeneous but there are significant differences between the countries considered: countries whose network indicators are closest to those expected in a homogeneous network are Poland, Romania, Sweden, Slovakia and Greece. However countries which are furthest from those that would prevail in a homogeneous network indicators are Germany, the Netherlands, France, Croatia and Slovenia.